Comparison of Cloud and Radiation Measurements to Models over the Southern Ocean at Escudero Station, King George Island - Cordero-Carrasco, R (American Geophysical Union, 2025)
Clouds and radiation play an important role in warming events over the Southern Ocean (SO). Here we evaluate European Center for Medium-Range Weather Forecasts Reanalysis version 5 (ERA5) and Polar Weather Research Forecast (PWRF) output through comparison to surface-based measurements of clouds, radiation, and the atmospheric state over the SO during 2017-2023 at Escudero Station (62.2 degrees S, 58.97 degrees W) on King George Island. ERA5 mean monthly downward shortwave (DSW) radiative fluxes are found to be 38-50 W m-2 higher than observations in summer, whereas ERA5 mean monthly downward longwave (DLW) is biased by -18 to -22 W m-2 in summer and -16 W m-2 on average over the year. Comparisons of temperature, humidity, and lowest-cloud base heights between ERA5 and observations rule these factors out as large contributors to the DLW flux biases. The similarity between observed DLW cloud forcing distributions for atmospheric columns containing low-level liquid and ice-only clouds suggests limited influence of cloud phase errors on DLW biases. Thus the most likely explanation for DLW flux biases in ERA5 is underestimated cloud optical depth, which is also consistent with DSW flux biases. Similar biases in ERA5 are found during atmospheric river (AR) events. By contrast, PWRF flux bias magnitudes are much smaller during AR events (-12 W m-2 for DSW and -2 W m-2 for DLW). After bias correction, ERA5 monthly average net cloud forcing over 2017-2023 is found to be a minimum of -107 W m-2 in January and a maximum of 65 W m-2 in June.